Aktivitas Enzim Peroksidase dan Kadar Klorofil pada Daun Angsana (Pterocarpus indicus) sebagai Peneduh Jalan yang terpapar Timbal - Anjar Astuti Ferdhiani; Sri Lestari; Elly Proklamasiningsih (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
One of emissions in the air that’s harmful to human health is lead ( Pb ). The negative effects caused by lead and then required solutions for reducing the metal, its called phytoremediation. The Plant which acts as an agent of phytoremediation is Angsana (Pterocarpus indicus Willd.). Research to find out the lead content in Angsana’s leaf at four locations, knowing the influence of exposure to lead against the activity of an enzyme peroxydases and chlorophyll content in the Angsana’s leaf. The location for collection of samples conducted in four location at Purwokerto (1) H.R Bunyamin, (2) Ovis Isdiman, (3) Gerilya, and (4) Dr. Soeharso. A method of the sample used purposive sampling. Sample were analysed using wet digestion method, then were analysed using Atomic Absorbance Spectrofotometer (AAS). The activity of peroxydases and levels of chlorophyll were analysed using spectrophotometer Uv Vis. Result showed that the lead content in Angsana’s leaf is 0,1 – 0, 25 mg/L, the activity of peroxidases is 600- 1250 unit/g and chlorophyll content is 9,0- 21,0 mg/L. The conclusion was no relations about chlorophyll content with levels of lead content and the relations about activity of enzymes peroxydases and lead content is low . Content of lead on Angsana’s leaf of research has been done do not reach 1000 mg/L.